Volatile Compounds Produced in Sterile Fish Muscle (Sebastes melanops) by Pseudomonas putrefaciens, Pseudomonas fluorescens, and an Achromobacter Species - Miller, A. (1973)
Volatile compounds produced by Pseudomonas putrefaciens, P. fluorescens, and an Achromobacter species in sterile fish muscle (Sebastes melanops) were identified by combined gas-liquid chromatography and mass spectrometry. Compounds produced by P. putrefaciens included methyl mercaptan, dimethyl disulfide, dimethyl trisulfide, 3-methyl-1-butanol, and trimethylamine. With the exception of dimethyl trisulfide, the same compounds were produced by an Achromobacter species. Methyl mercaptan and dimethyl disulfide were the major sulfur-containing compounds produced by P. fluorescens.